Musical subcultures and Costa Rican urban popular culture in the documentaries Vargas Brothers and Se prohíbe bailar “suin” - Cuvardic García, Dorde (2020)
In documentary history, popular music has had a relevant place. A large group of documentaries is dedicated to the professional and private trajectory of musicians, dealing with exhaustion from touring, as well as drug consumption, etc., while another group focuses its attention on the consumption practices of popular music (fans).  Costa Rican documentaries show examples from both venues, in the frame of Central American modernity: the redemption of a rock and roll band, after their journey to drugs and alcohol, in Los Vargas Brothers, and the consumption (dance) of a genre considered marginal for a long time, the ‘swing criollo’, in Se prohíbe bailar suin. Costa Rican urban popular culture is represented in both documentaries.